Free Convection Heat Transfer Around a Cylinder Embedded in an Enclosure Filled with Porous Media - Rasheed, Suhad A.; Mahmood, Abeer Aamer (Al-Nahrain Journal for Engineering Sciences, 2020)
An experimental and theoretical study of free convection heat transfer for a cylinder placed in an iron test section of dimensions  (0.2x0.2x0.2 m3), the test section filled with saturated porous material glass balls   (5 mm), and the air is the working fluid with Raleigh number (7692.6 ? Ra ? 17654). The circular cylinder heater (D = 0.015 m, L = 0.2 m) is heated electrically, made of Copper and located in different positions (in X & Y direction). The theoretical part includes solving the free convection heat transfer using the ANSYS program (fluent). The experimental and theoretical results showed that the surface temperature values around the cylinder perimeter when changing its position within the test section are changing as moving up and down where the effect of buoyancy force appears. The maximum difference between the upper and lower position at the experimental result is 7.22%, and the average Nusselt number increases with Raleigh number and heat flux. Also, the experimental results showed that the use of porous material significantly improves the heat transfer by 48.6%. The maximum percentage change between the experimental and theoretical results is 5.46%. Moreover, experimental correlations were achieved, and a comparison was performed between the present results with the previous studies and it gives a good agreement.